Case Report: Role of numerical simulations in the management of acute aortic syndromes - Rizza, Antonio; Castiglione, Vincenzo; Capellini, Katia; Palmieri, Cataldo; Gasparotti, Emanuele; Berti, Sergio; Celi, Simona (Frontiers in Cardiovascular Medicine, 2024)
Penetrating aortic ulcer (PAU) represents a subset of acute aortic syndromes characterized by high rupture risk and management challenges, particularly in elderly patients with significant comorbidities. This case report showcases a 75-year-old patient with a history of coronary artery bypass graft (CABG) and with multiple PAUs involving the aortic arch, deemed unfit for conventional open surgery. A branched aortic endograft with a pre-cannulated side component for the left subclavian artery (LSA) was employed to preserve the patency of the previous CABG. Two computational fluid dynamics (CFD) simulations and a morphological analysis were performed on the pre- and post-intervention aortic configurations to evaluate changes in flow rate and pressure drop at LSA level and differences in the lumen size. The results revealed a decrease in the flow rate equal to 2.38% after the intervention and an increase in pressure drop of 4.48 mmHg, while the maximum differences in LSA cross-sectional areas and diameters were 1.49 cm2 and 0.64 cm, respectively. Minimal alteration in LSA blood flow due to the chosen intervention approach confirmed the effectiveness of the selected unibody design endograft with LSA preservation, ensuring myocardial perfusion. Therefore, CFD simulations demonstrate to be a powerful tool to evaluate the hemodynamic consequences of interventions by accurately estimating the main fluid dynamic parameters.